1999
DOI: 10.1002/(sici)1521-2254(199903/04)1:2<111::aid-jgm22>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Polycation-based DNA complexes for tumor-targeted gene delivery in vivo

Abstract: For systemic application, the physical and colloidal parameters of the transfection complexes, such as particle size, stability, and surface charge, determine DNA biodistribution, toxicity, and transfection efficacy. By controlling these parameters, DNA biodistribution and gene expression can be targeted to different organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 12 publications
3
95
0
Order By: Relevance
“…Following intravenous application in SCID mice, analysis of luciferase distribution in both models showed that expression levels within the tumors were up to 2 logs higher than levels found in the liver, which was the highest expressing major organ, with expression in the tumor accounting for 97% to 99% of the total transgene expression measured in vivo. Notably, no acute toxicity, as reported for positively charged DNA/PEI particles, 13,14 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Following intravenous application in SCID mice, analysis of luciferase distribution in both models showed that expression levels within the tumors were up to 2 logs higher than levels found in the liver, which was the highest expressing major organ, with expression in the tumor accounting for 97% to 99% of the total transgene expression measured in vivo. Notably, no acute toxicity, as reported for positively charged DNA/PEI particles, 13,14 was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the differences remain to be clarified; reporter gene expression may not be in direct correlation to the body distribution pattern, as previously described. 24,25 In the current case, positive charges of polyplexes cannot be the sole explanation for the observed gene expression patterns since HD O at c/p ratio of 2 still shows a more favorable tumor/lung relation as compared to LPEI.…”
Section: Gene Expression In Vivomentioning
confidence: 99%
“…16,17 Intravenous administration of genes in mice mediated by PEGylated Tf-PEI/DNA complexes could result in a high expression of exogenous genes in tumor but in tail as well. 18 Here, we described the successful gene transfer into subcutaneously transplanted tumors via systemic administration of the GE7 system. Our results demonstrated that high b-gal activity could be observed in tumor tissues and the expression there persisted for more than 2 weeks.…”
Section: Discussionmentioning
confidence: 99%